A New Approach for Determining the Cost Allocation by Considering Transmission Line Mutual Inductance for Multilateral Contracts - Suma Deepthi; V. Sumadeepthi; K. Rama (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
Addressing loss due to transmission and its cost allocation in deregulated electricity market is an  essential issue. Independent System Operator (ISO) provides the active power loss from the generators and the associated cost is allocated to the concerned parties in a fair way. The generators and loads participate in the loss/cost allocation process. The highlight of the paper is that the effect of mutual inductance (MI) that exists on transmission line in transmission loss/cost allocation process for multlateral contracts is illustrated. To demonstrate the effect of mutual inductance, the results of  existing loss allocation methods like penalized quoted cost (PQC) based approach are discussed. Effect of mutual inductance is presented using an IEEE 30 bus system. The simulation results are carried out using MATLAB R2014a. The result shows that mutual inductance has a significant impact on transmission loss and hence cannot be ignored.